Effect of Early Intervention Programs on Developmental Delays in Infants and Toddlers in Malawi - Chisomo, Yvonne (Global Journal of Health Sciences, 2024)
Purpose: The aim of the study was to analyze the effect of early intervention programs on developmental delays in infants and toddlers in Malawi. Methodology: This study adopted a desk methodology. A desk study research design is commonly known as secondary data collection. This is basically collecting data from existing resources preferably because of its low cost advantage as compared to a field research. Our current study looked into already published studies and reports as the data was easily accessed through online journals and libraries. Findings: Early intervention programs in Malawi for developmental delays in infants and toddlers have shown significant positive outcomes. These programs, integrated into community healthcare services, focus on early identification, assessment, and tailored interventions. They improve motor skills, language development, cognitive abilities, and social-emotional skills. Parental involvement is crucial, with caregivers educated to support developmental progress at home. Unique Contribution to Theory, Practice and Policy: Ecological systems theory, social learning theory & bioecological model of development may be used to anchor future studies on effect of early intervention programs on developmental delays in infants and toddlers in Malawi. Enhance the involvement of parents and caregivers in EIPs through structured training and support. Advocate for increased funding and resource allocation to support the expansion and sustainability of EIPs. Policy recommendations should focus on securing public and private investments in early childhood development, prioritizing programs that demonstrate evidence-based effectiveness.